Silicon Nitride Based Non-Volatile Memory Structures with Embedded Si or Ge Nanocrystals - Zsolt J. Horvath; P. Basa; T. Jaszi; A. E. Pap; Gy. Molnar; A. I. Kovalev; D. L. Wainstein; T. Gerlai; P. Turmezei (Communications - Scientific letters of the University of Zilina, 2010)
Memory structures with an embedded sheet of separated Si or Ge nanocrystals were prepared by low pressure chemical vapour deposition using a Si3N4 control and SiO2 tunnel layers. It was obtained that a properly located layer of semiconductor nanocrystals can improve both the charging and retention behaviour of the MNOS structures simultaneously. Memory window width of above 6 V and retention time of 272 years was achieved for charging pulses of 15 V, 10 ms.